2010
DOI: 10.3382/ps.2010-00665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat sources on fatty acid deposition and lipid metabolism in broiler chickens

Abstract: The hypothesis tested was that dietary vegetable fats rich in saturated fatty acids, when compared with a vegetable oil rich in linoleic acid, increase fat deposition in broiler chickens and affect synthesis or oxidation, or both, of individual fatty acids. Diets with native sunflower oil (SO), a 50:50 mix of hydrogenated and native SO, palm oil, and randomized palm oil were fed to broiler chickens. Intake of digestible fat and fatty acids, whole body fatty acid deposition, hepatic fatty acid profile, and hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 30 publications
7
48
1
Order By: Relevance
“…Therefore, the slopes of the regression between tissue and dietary MCFAs and EFAs may represent the AR of these FAs in the tissues. Except that the AR of C18:2 is lower in the breast meat (i.e., 0.46), that of C18:2 and C18:3 in the thigh meat and abdominal fat (Table 3) is comparable with the values of 0.7 and 0.5, respectively (Villaverde et al, 2006;Smink et al, 2010). We found that the AR of MCFAs was less than 0.5 in the breast meat, thigh meat and abdominal fat.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, the slopes of the regression between tissue and dietary MCFAs and EFAs may represent the AR of these FAs in the tissues. Except that the AR of C18:2 is lower in the breast meat (i.e., 0.46), that of C18:2 and C18:3 in the thigh meat and abdominal fat (Table 3) is comparable with the values of 0.7 and 0.5, respectively (Villaverde et al, 2006;Smink et al, 2010). We found that the AR of MCFAs was less than 0.5 in the breast meat, thigh meat and abdominal fat.…”
Section: Resultssupporting
confidence: 63%
“…The contents of EFAs and LCFAs shown in breast meat, thigh meat, and abdominal fat ( (Crespo and Esteve-Garcia, 2001;Smink et al, 2010). However, the contents of nonessential fatty acids (NEFAs) in the breast meat, thigh meat, and abdominal fat (Table 2) increased as the dietary MCTs increased (P<0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Hilda [15] found 0.50 % of arachidonic acid in chicken fat and Guntarti et al [16] also explained that this was likely due to the arachidonic acid was lost by heating or derivatization during the extraction process. Smink et al [17] reported that chicken fat has high linoleic acid (omega-6 fatty acid) with percentages of 7.9-22.8 %. This can be seen that linoleic acid in GCMS results has percentage of about 15 % and it is one of dominant fatty acids in chicken fat.…”
Section: Fatty Acid Composition Of Chicken Fat Using Gcmsmentioning
confidence: 99%
“…Liver is where MUFA is synthesized. The presence of PUFAs in the diet leads to lower conversion of SFA into MUFA due to inhibitary effects of PUFAs on the activity of the enzyme Δ9-desaturase in the liver (Ajuyah et al, 1991;Lopez-Ferrer et al, 2001a,b;Villaverde et al, 2006;Smink et al, 2010). The high concentration of LA (18:2n-6) in the diet with only sunflower oil was reflected in its significantly greater incorporation into thigh and breast muscle compared with the 100% rapeseed oil dietary group (p=0.001).…”
Section: Effects Of Dietary Inclusion Of Oil Sources With or Without mentioning
confidence: 99%